Evaluation of Cercospora oryzae Miyake under natural pressure conditions - GNANCADJA, ANDRÉ LÉOPOLD SIMPLICE; SOURA, HERVE; Koita, Kadidia; GANDONOU, Christophe Bernard; BABA-MOUSSA, FARID A. KADER SAÏD (My University, 2020)
Objective: This study is a contribution to the knowledge of Cercospora oryzae Miyake, in order to increase yields. It will consist in: i) evaluating the resistance of five varieties of rice, ii) evaluating the effect of Cercospora oryzae Miyake on the leaf and panicle stages and iii) evaluating the yield. Methodology and results: The study will combine phenotypic and agromorphological tools. On the ninety first (91th) day after sowing, a high incidence of leaf Cercosporiosis was recorded on the varieties TS2 (29.74%), FKR34 (27%) and a very low incidence on the variety ORYLUX6 (5, 78%). From tillering to panicle initiation, the rate of progression of the epidemic r2 = 0.879 is significant in TS2. The ORYLUX6 variety is the most capable of slowing the progression of the epidemic. At the panicular level, from the pasty grain stage to the milky grain stage, the incidence has increased for most of the varieties. The ORYLUX6 recorded the highest yield with 4.38 t/ ha. Conclusion and application potential of the results: Cercospora oryzae Miyake causes a drop in yieldby reducing the leaf area of thr leaves. Cercospora oryzae Miyake is an important disease of rice in Sud- Benin. These results constiyute a stage of an in-depth research work on the characterization (agronomic and genetic) of Cercospora oryzae Miyake in order to propose methods of control.
Keywords: Cercospora oryzae; incidence; yield; rice; Benin